Chlorambucil plus ofatumumab versus chlorambucil alone in previously untreated patients with chronic lymphocytic leukaemia (COMPLEMENT 1): a randomised, multicentre, open-label phase 3 trial. Issue 9980 (9th May 2015) - Hillmen, Peter; Robak, Tadeusz; Janssens, Ann; Babu, K Govind; Kloczko, Janusz; Grosicki, Sebastian; Doubek, Michael; Panagiotidis, Panagiotis; Kimby, Eva; Schuh, Anna; Pettitt, Andrew R; Boyd, Thomas; et al.
Summary: Background: Treatment for patients with chronic lymphocytic leukaemia who are elderly or who have comorbidities is challenging because fludarabine-based chemoimmunotherapies are mostly not suitable. Chlorambucil remains the standard of care in many countries. We aimed to investigate whether the addition of ofatumumab to chlorambucil could lead to better clinical outcomes than does treatment with chlorambucil alone, while also being tolerable for patients who have few treatment options. Methods: We carried out a randomised, open-label, phase 3 trial for treatment-naive patients with chronic lymphocytic leukaemia in 109 centres in 16 countries. We included patients who had active disease needing treatment, but in whom fludarabine-based treatment was not possible. We randomly assigned patients (1:1) to receive oral chlorambucil (10 mg/m 2 ) on days 1–7 of a 28 day treatment course or to receive chlorambucil by this schedule plus intravenous ofatumumab (cycle 1: 300 mg on day 1 and 1000 mg on day 8; subsequent cycles: 1000 mg on day 1) for three to 12 cycles. Assignment was done with a randomisation list that was computer generated at GlaxoSmithKline, and was stratified, in a block size of two, by age, disease stage, and performance status. The primary endpoint was progression-free survival in the intention-to-treat population and assessment was done by an independent review committee that was masked to group assignment. The study is registered withClinicalTrials.gov, numberNCT00748189 . Findings: We enrolled 447 patients, median age 69 years (range 35–92). Between Dec 22, 2008, and May 26, 2011, we randomly assigned 221 patients to chlorambucil plus ofatumumab and 226 patients to chlorambucil alone. Median progression-free survival was 22·4 months (95% CI 19·0–25·2) in the group assigned to chlorambucil plus ofatumumab compared with 13·1 months (10·6–13·8) in the group assigned to chlorambucil only (hazard ratio 0·57, 95% CI 0·45–0·72; p<0·0001). Grade 3 or greater adverse events were more common in the chlorambucil plus ofatumumab group (109 [50%] patients; vs 98 [43%] given chlorambucil alone), with neutropenia being the most common event (56 [26%] vs 32 [14%]). Grade 3 or greater infections had similar frequency in both groups. Grade 3 or greater infusion-related adverse events were reported in 22 (10%) patients given chlorambucil plus ofatumumab. Five (2%) patients died during treatment in each group. Interpretation: Addition of ofatumumab to chlorambucil led to clinically important improvements with a manageable side-effect profile in treatment-naive patients with chronic lymphocytic leukaemia who were elderly or had comorbidities. Chlorambucil plus ofatumumab is therefore an important treatment option for these patients who cannot tolerate more intensive therapy. Funding: GlaxoSmithKline, Genmab A/S.